Innate lymphoid cells (ILC) in SARS-CoV-2 infection. (August 2021) - Kumar, Amrita; Cao, Weiping; Endrias, Kedan; Kuchipudi, Suresh V.; Mittal, Suresh K.; Sambhara, Suryaprakash
Abstract: Innate Lymphoid Cells (ILCs) are a class of innate immune cells that form the first line of defense against internal or external abiotic and biotic challenges in the mammalian hosts. As they reside in both the lymphoid and non-lymphoid tissues, they are involved in clearing the pathogens through direct killing or by secretion of cytokines that modulate the adaptive immune responses. There is burgeoning evidence that these cells are important in clearing viral infections; therefore, it is critical to understand their role in the resolution or exacerbation of the disease caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2). In this review, we summarize the recent findings related to ILCs in response to SARS-CoV-2 infections.